Relationship Between Knowledge And Anxiety Of Primiparous Postpartum Mothers In Newborn Care - Muldaniyah Muldaniyah; Lia Fitria; Hayatul Rahimah; Riswanti Riswanti; Naning Suryani (International Journal Of Health Science, 2023)
The suboptimal handling and care of newborns are among the factors contributing to perinatal mortality. One of the reasons for the suboptimal handling and care of newborns is the lack of knowledge among mothers about newborn care, especially among primiparous mothers who lack direct experience in caring for newborns. This situation leads to maternal anxiety during the first week of the baby's life. The objective of this study is to determine the relationship between knowledge and anxiety among primiparous postpartum mothers in the care of newborns at the North Buton Regional General Hospital. The research design used is analytical, employing a Cross-Sectional study approach with a sample size of 30 postpartum mothers. Data collected include both primary and secondary sources, and the data analysis involves the chi-square statistical test. The research results indicate a correlation between maternal knowledge and anxiety among primiparous postpartum mothers in the care of newborns, with a p-value of 0.003 < α = 0.000. Consequently, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. In other words, there is an influence of knowledge on the anxiety levels of first-time postpartum mothers in the care of newborns at the North Buton Regional General Hospital.